Regulation of seed germination and seedling growth by chemical signals from burning vegetation - Nelson, D.; Flematti, G.; Ghisalberti, E.; Dixon, Kingsley; Smith, S. (2012)
It is well known that burning of vegetation stimulates new plant growth and landscape regeneration. The discovery that char and smoke from such fires promote seed germination in many species indicates the presence of chemical stimulants. Nitrogen oxides stimulate seed germination, but their importance in post-fire germination has been questioned. Cyanohydrins have been recently identified in aqueous smoke solutions and shown to stimulate germination of some species through the slow release of cyanide. However, the most information is available for karrikins, a family of butenolides related to 3-methyl-2H- furolsqb2,3-crsqbpyran-2-one. Karrikins stimulate seed germination and influence seedling growth. They are active in species not normally associated with fire, and in Arabidopsis they require the F-box protein MAX2, which also controls responses to strigolactone hormones. We hypothesize that chemical similarity between karrikins and strigolactones provided the opportunity for plants to employ a common signal transduction pathway to respond to both types of compound, while tailoring specific developmental responses to these distinct environmental signals.